PEKERJA SOSIAL SEBAGAI AGEN PERUBAHAN DALAM PENANGGULANGAN KEMISKINAN: PERSPEKTIF PANCASILA - Marpaung, Riffani Nursiah Melni (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
Poverty has become a multidimensional challenge that not only affects the economy, but also health, education, and relationships in society. In Indonesia, poverty alleviation requires an approach that is related to the nation's noble values, as reflected in Pancasila. This article aims to analyze the role of social workers' strategies in overcoming poverty through approaches based on Pancasila values. By using the principles of humanity, social justice, and mutual cooperation, social workers are not only companions, but also agents of change that can encourage community empowerment.